QT DISPERSION IN PATIENTS WITH CORONARY ARTERY DISEASE - Mubarak, Sadia; Majeed, Syed Muhammad Imran; Khan, Muhammad Alamgir (Pakistan Journal of Physiology, 2015)
QT dispersion is the difference between the longest and the shortest QT intervals as measured from the 12 lead standard ECG. It reflects ventricular repolarisation heterogeneity which may lead to ventricular arrhythmias in certain cases. Myocardial ischemia plays a central role in the pathophysiology of prolonged QT dispersion leading to re-entrant type ventricular arrhythmias. Current study was planned to find out frequency of patients with increased QT dispersion in coronary artery disease patients and to compare QT dispersion in these patients with standard normal value. Methods: 43 Patients having coronary artery disease with at least one stenotic lesion of greater than 70% of the vessel lumen were included. Patients with diabetes mellitus, systemic arterial hypertension, structural heart diseases and bundle branch block were excluded. DMS 300 4A Holter monitors were used to obtain 12 lead digital ECG recordings. CardioScan premium luxury software was used for analysis of QT dispersion. Results: Six (14%) patients had normal whereas 37 (86%) had prolonged QT dispersion and the difference was significant (p<0.001). QT dispersion in coronary artery disease patients (46.6Â±11.20 ms) was significantly increased as compared to normal reference value of 33.4 ms (p<0.001). Conclusion: Patients with coronary artery disease have significantly prolonged QT dispersion which may put them at risk of arrhythmogenesis.